Integrasi Akuntansi Lingkungan Dalam Mewujudkan Keberlanjutan Program Makan Bergizi Gratis (MBG) Pada SPPG Kalangsurya - Siska Kusuma Wardani; Rohma Septiawati; Avincennia Vindy Fitriana (ISAS, 2026)
This study aims to examine how environmental accounting integration can achieve sustainable implementation of the Free Nutritious Meals (MBG) program at the SPPG Kalangsurya in Karawang Regency. The research method used in this study was qualitative, utilizing interviews, observation, and documentation. The results show that practices such as waste sorting, implementing hygiene SOPs, using environmentally friendly food trays, and collaborating with the Environmental Agency reflect sound environmental accounting principles, but environmental costs have not been recorded separately. Although environmental costs have not been recorded separately, the SPPG Kalangsurya recognizes that environmental accounting is not only a compliance tool but also a sustainability strategy that can improve efficiency, reputation, and public trust in the implementation of the Free Nutritious Meals (MBG) program. The main challenges for the SPPG Kalangsurya are a lack of understanding of environmental accounting and the absence of a dedicated recording system. However, there are opportunities to achieve long-term business sustainability. Keywords: Environmental Accounting, Business Sustainability, Free Nutritious Meals